From mega to low-tech: What Signifies strong sustainability Energy Systems in Eastern Africa? - (:unkn) unknown (My University, 2023)
In East Africa, domestic energy is provided by a variety of socio-techniques, ranging from firewood and charcoal to mega-projects (wind power, geothermal energy). These socio-techniques are criticized for their socio-ecological consequences (vegetation cover, health) and their social inefficiency. Using an STS methodology, "Socialized Energy" explores energy vulnerability based on alternatives that combine appropriate technologies and participation, from a "strong sustainability" perspective in East Africa.
Keywords: African Research